J/ψ production at midrapidity in p-Pb collisions at √sNN=8.16 TeV - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Crkovská, Jana; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Kim, Minjung; Kroesen, Martin; Nath, Abhishek; et al. (Journal of high energy physics, 2023)
The production of inclusive, prompt and non-prompt J/ψ was studied for the first time at midrapidity (−1.37 < ycms < 0.43) in p-Pb collisions at √s NN= 8.16 TeV with the ALICE detector at the LHC. The inclusive J/ψ mesons were reconstructed in the dielectron decay channel in the transverse momentum (pT) interval 0 < pT < 14 GeV/c and the prompt and non-prompt contributions were separated on a statistical basis for pT > 2 GeV/c. The study of the J/ψ mesons in the dielectron channel used for the first time in ALICE online single-electron triggers from the Transition Radiation Detector, providing a data sample corresponding to an integrated luminosity of 689 ± 13 μb−1. The proton-proton reference cross section for inclusive J/ψ was obtained based on interpolations of measured data at different centre-of-mass energies and a universal function describing the pT-differential J/ψ production cross sections. The pT-differential nuclear modification factors RpPb of inclusive, prompt, and non-prompt J/ψ are consistent with unity and described by theoretical models implementing only nuclear shadowing.
Gesehen am 16.11.2023
Veröffentlicht: 17. Juli 2023
*The ALICE collaboration: S. Archaya, V. Anguelov, A. Berdnikova, L. Bergmann, J. Crkovská, M.C. Danisch, V.J.G. Feuillard, I. Fokin, P. Glässel, M. Kim, M. Kroesen, A. Nath, Y. Pachmayer, K. Reygers, R. Schicker, A. Schmah, G. Skorodumovs, J. Stachel, S.F. Stiefelmaier, C.A. van Veen, M.A. Völkl, B. Windelband, A. Yuncu, F. Zanone [und sehr viele weitere Personen]
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol
Im Titel ist "psi" als griechischer Buchstabe dargestellt